Analisis Ketimpangan Pembangunan dan Klasifikasi Wilayah antar Kabupaten/Kota Provinsi Jawa Barat Tahun 2016-2020 - Rizal Syaifudin; Aprilia Dwi Verliana; Sugeng Setyadi; Deris Desmawan (Forum Kerjasama Pendidikan Tinggi, 2022)
Economic growth between regencies/cities in West Java Province on 2016-2020 is different, this indicates that there is development inequality. The purpose of this study was to determine the level of development inequality and regional classification based on per capita income and economic growth between districts/cities in West Java Province on 2016-2020. This study uses the Williamson Index analysis approach and the Klassen Typology analysis. The results of this study indicate that the average development inequality between regencies/cities in West Java Province in 2016-2020 is 0.65802. These results indicate that development inequality is still relatively high. Based on the results of Klassen's Typology analysis, most areas in West Java Province are included in the Developing Regions group. These areas include Majalengka Regency, Kuningan Regency, Sumedang Regency, Bandung Regency, Cianjur Regency, Tasikmalaya Regency, Sukabumi Regency, Bogor Regency, Tasikmalaya City, Depok City, Banjar City, Pangandaran Regency, Ciamis Regency, and Bogor City. It is hoped that local governments can formulate policies and strategies in utilizing and managing the potential of each region as well as increasing investment in order to improve the process of regional economic growth in an effort to equalize development.